Emptio puellae Ravennae facta (Estudio y traducción de la tablilla editada por Cavenaile, CPL nº 193) - Martín Ferreira, Ana Isabel (Cuadernos de Filología Clásica. Estudios Latinos, 2008)
In this paper, we study and translate the document that certifies the buy and selling of a slave-woman, written in Latin with some Greek characters also included, preserved in a wax writing-tablet edited by Cavenaile (CPL 193). Apart from contributing with some conjectures that facilitate its understanding, we have also undertaken its dating and some particular judicial aspects, concluding with the linguistic commentary of the text from the perspective of Vulgar Latin.